I folkets tjeneste: Public service som omstridt begreb - Mouritsen, Per (Journalistica, 2006)
The concept of public service has always been contested. A history of the concept shows at least five different uses or meanings since the early nineties. Public service may refer to the democratic education of citizens, cultural enlightenment in a variety of senses of Bildung, or to integration in a national heritage. It may be employed as the ‘broad’ concept of public service, meaning a mixture of quality and something for everybody, which makes it possible to keep viewers and listeners loyal to a particular channel. Finally, TV 2 has given the concept a new liberal-populist meaning of ‘meeting the people where it is’. The analysis shows that several of these meanings are diametrically opposed to each other.